Vertical coordination, rent distribution, and development - Johan F. M. Swinnen; Anneleen Vandeplas (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2007)
Vertical coordination has grown strongly in global supply chains. Local suppliers in developing countries engage in complex contracting with companies selling into high-income markets - either domestically or internationally. These contracts not only specify conditions for delivery and production processes, but also include the provision of inputs, technology, management advice etc. This paper analyzes how weak contract enforcement institutions and imperfect factor markets are affecting vertical coordination in development, and what the implications are for income creation and rent distribution.
Keywords: C78; D23; O12; Q12; 330; Vertical coordination; contract enforcement; development; rent distribution; Internationaler Wettbewerb; Standortfaktor; Entwicklung; Institutionelle Infrastruktur; Entwicklungsländer